The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1365-2249.1995.tb03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tumour necrosis factor-alpha (TNF-α) mRNA in bladders and spleens of mice after intravesical administration of bacillus Calmette-Guérin

Abstract: SUMMARYIntravesical bacillus Calmette-Guerin (BCG) therapy is highly eflfective in the therapy of carcinoma in situ of the bladder, but the mechanism of BCG immunotherapy is not clearly understood. We studied the production of TNF-n in spleens and bladders ofmice after intravesical BCG or BCG/interferon-gamma (iFN--}) instillation. Significant change of TNF-a mRNA expression of spleens and bladders of C3H/He mice was observed after intravesical BCG instillation, although intravesical IFN-7 therapy 3 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
(25 reference statements)
0
2
0
2
Order By: Relevance
“…While absence of p53 can be attributed to the reduced TNF-α responses and diminished p53 functions in HCT116 p53 -/- cells, the possible reasons for the observations in MDA-MB-231 with mutant p53 is currently under investigation. Further, though BCG treatment, by itself, can induce the expression of TNF-α in immune cells [ 23 ] and during BCG therapy [ 49 ], in the current study we addressed the ability of BCG to revert the TNF-α responses such as apoptosis during therapy. However, BCG failed to protect A549 cells against apoptosis induced by other death ligands of the TNF family such as TRAIL (Additional file 2 : Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…While absence of p53 can be attributed to the reduced TNF-α responses and diminished p53 functions in HCT116 p53 -/- cells, the possible reasons for the observations in MDA-MB-231 with mutant p53 is currently under investigation. Further, though BCG treatment, by itself, can induce the expression of TNF-α in immune cells [ 23 ] and during BCG therapy [ 49 ], in the current study we addressed the ability of BCG to revert the TNF-α responses such as apoptosis during therapy. However, BCG failed to protect A549 cells against apoptosis induced by other death ligands of the TNF family such as TRAIL (Additional file 2 : Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…IL‐2, IFN‐γ, and TNF are potent pro‐inflammatory cytokines that are associated with antigen recognition. Animal and in vitro model investigations have demonstrated that effective immunotherapy with BCG involves a shift of cytokine responses toward Th1 (19–22). Furthermore, this immune activation may be persistent.…”
Section: Intravesical Use Of Bcgmentioning
confidence: 99%
“…Die BCGBehandlung führt zur vermehrten IFN-γ-Expression und zur Herunterregulation von IL-4, was die Induktion eines T H 1-Zytokin-Profils, ähnlich der Situation im Menschen, nahe legt [36]. In einem vergleichbaren Modell induzierte BCG zusätzlich die Expression von TNF-α [56]. …”
Section: Worin Liegt Die Funktionelle Relevanz Der Induktion Von Haupunclassified